(untitled) (Research, Society and Development, 2021)
The use of stimulating products in the production of vegetables is of great importance for a better establishment of seedlings in the field, a factor directly related to seed germination. The aim of this study was to verify the effects of different biological products stimulating plant development such as Ascophylum nodosum, Ecklonia maxima, Brutal® (Complex of microorganisms) and Serenade® (Bacillus subtilis) on the performance of vegetables, in comparison with the imbibition of seeds with Water and Potassium Nitrate (0.2% KNO3). The products were applied to the seeds at a dose of 150 mL / kg of seeds, making the mixture manually until uniform for later sowing. Seeds of four cultivars of lettuce, Americana, Aurélia, Crespa Repolhuda and Crespa de Verão were used and six treatments forming a 6x4 factorial in a completely randomized design. Germination tests, first count, cold test, accelerated test and seedling dry matter were carried out. It was concluded that the products influenced the first germination count and total germination, germination speed index with improved performance in less vigorous seeds. The cold test showed better seed performance in relation to the accelerated test and seedling dry matter test. In high vigor seeds, the effects of seed treatments on performance were not evident.